Investigating the Impact of a Musical Intervention on Preschool Children’s Executive Function - Alice Bowmer; Kathryn Mason; Julian Knight; Graham Welch (Frontiers in Psychology, 2018)
The impact of music interventions on the cognitive skills of young children has become the focus of a growing number of research studies in recent years. This study investigated the effect of weekly musicianship training on the executive function abilities of 3-to-4-year-old children at a London, United Kingdom preschool, using a two-phase experimental design. In Phase 1, 14 children (Group A) took part in eight weekly musicianship classes, provided by a specialist music teacher, while 25 children (Groups B and C combined) engaged in nursery free play. Results of this Phase showed Group A to have improved on two measures relating to planning and inhibition skills. During Phase 2, Group A continued with music classes, while Group B began music classes for the first time and Group C took part in an art intervention. Repeated measures ANOVA found no significant difference in performance improvement between the three participant groups during phase 2; however, the performance difference between groups was nearing significance for the peg tapping task (p = 0.06). The findings from this study contribute to current debates about the potential cognitive benefit of musical interventions, including important issues regarding intervention duration, experimental design, target age groups, executive function testing, and task novelty.